Reflections About The Importance Of Technology In The Professional Of The Future (Journal of Namibian Studies : History Politics Culture, 2022)
The present time demands the education of a competent professional in the use of information and communication technologies, this paper aims to reflect on the education that future professionals are having in the field of ICTs, determining whether undergraduate programs include in their curricula elements related to computer tools, which strengthen their occupational performance. For the approach of this research, the qualitative method was chosen, and the data collection was done through a survey that was applied virtually, in which it was possible to know the opinions of the participants regarding the topics covered in this analysis. It is concluded by recognizing the need to take as a central axis the application and use of technologies that strengthen the professional and occupational profile within the curricular spaces that are part of the programs offered by the university educational institutions.